An examination of the health and wellbeing of childless women: A cross-sectional exploratory study in Victoria, Australia - Graham Melissa L; Hill Erin; Shelley Julia M; Taket Ann R (BMC, 2011)
Abstract Background Childlessness among Australian women is increasing. Despite this, little is known about the physical and mental health and wellbeing of childless women, particularly during the reproductive years. The aims of this exploratory study were to: 1) describe the physical and mental health and wellbeing and lifestyle behaviours of childless women who are currently within the latter part of their reproductive years (30 - 45 years of age); and 2) compare the physical and mental health and wellbeing and lifestyle behaviours of these childless women to Australian population norms. Methods A convenience sample of 50 women aged between 30 and 45 years were recruited to participate in a computer assisted telephone interview. The SF-36 Health Survey v2 and lifestyle indicators were collected in regards to women's health and wellbeing. Data were analysed using descriptive statistics, t-tests for independent sample means and 95% confidence intervals for the difference between two independent proportions. Results Childless women in this study reported statistically significant poorer general health, vitality, social functioning and mental health when compared to the adult female population of Australia. With the exception of vegetable consumption, lifestyle behaviours were similar for the childless sample compared to the adult female population in Australia. Conclusions Childless women may be at a greater risk of experiencing poor physical and mental health when compared to the Australian population. A woman's health and wellbeing during her reproductive years may have longer term health consequences and as such the health and wellbeing of childless women requires further investigation to identify and address implications for the provision of health (and other social) services for this growing population group.